2016
DOI: 10.1021/acs.energyfuels.6b01728
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Properties of the Decarboxylation Products of Oleic Acid by Catalytic Triruthenium Dodecacarbonyl

Abstract: Recently, ruthenium-catalyzed isomerization–decarboxylation of fatty acids to give alkene mixtures was reported. When the substrate was oleic acid, the reaction yielded a mixture consisting of heptadecene isomers. In this work, we report the compositional analysis of the mixture obtained by triruthenium dodecacarbonyl catalyzed decarboxylation of oleic acid. Surprisingly, the most prominent single compound identified was heptadecane at approximately 18 wt %. A mixture of heptadecene isomers constituted the gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
(85 reference statements)
3
20
0
Order By: Relevance
“…The GC–MS analyses (see Figure 1 for a typical chromatogram with the products formed from palmitic acid as example) revealed that the same classes of compounds, an alkane, all possible alkene isomers, alkadienes, and alkylaromatics, observed previously in work on decarboxylation of oleic acid in the presence of Ru 3 (CO) 12 40 are formed in all reactions. The pattern of the reaction products appears to depend on neither the chain length, similar to the results regarding hydrothermal deoxygenation with Pt/C, 37 nor the number of double bonds and their position and configuration.…”
Section: Results and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The GC–MS analyses (see Figure 1 for a typical chromatogram with the products formed from palmitic acid as example) revealed that the same classes of compounds, an alkane, all possible alkene isomers, alkadienes, and alkylaromatics, observed previously in work on decarboxylation of oleic acid in the presence of Ru 3 (CO) 12 40 are formed in all reactions. The pattern of the reaction products appears to depend on neither the chain length, similar to the results regarding hydrothermal deoxygenation with Pt/C, 37 nor the number of double bonds and their position and configuration.…”
Section: Results and Discussionsupporting
confidence: 63%
“…Essential fuel properties of the product mixture obtained from oleic acid were determined previously. 40 The cetane number was 86.9, the kinematic viscosity at 40 °C was 3.14 mm 2 /s, the cloud point (CP) was −1 °C, the pour point (PP) was −4 °C, the oxidative stability by the so-called Rancimat test was 3.4 h, the density at 15 °C is 791 kg/m 3 , and the wear scar in the high-frequency reciprocating rig lubricity test is 299 μm. Although no properties were determined here for the products derived from the other fatty acids and alkenes, it can be observed that the products with high amounts of alkane and lower amounts of alkenes would likely have more problematic cold flow properties (higher CP and PP) but improved oxidative stability, whereas the converse would hold for the products with reduced amounts of alkane but therefore greater amounts of alkenes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A 60% yield of 10-undecenoic acid was achieved under the conditions of 0.89 wt % Ru 3 (CO) 12 at 250 C and 4 h duration (Muench et al, 2016). Moser et al (2016) further reported that 77.6% heptadecene and 18.0% heptadecane was obtained by Ru-catalyzed DCX/DCN of fatty acids. There were also other reactions such as the decarboxylation, dehydrogenation, isomerization, hydrogenation, and cyclization/aromatization took place, which made a mixture of predominantly alkenes (Knothe et al, 2017).…”
Section: Organometallic Precursor Catalystsmentioning
confidence: 80%
“…Due to the relatively low yield of MAA given by manganese­(II) oxalate along with evolution of carbon monoxide, ruthenium catalysis was explored. Ruthenium carbonyl carboxylates were of interest because of our previous work on tandem isomerization–decarboxylation of oleic acid. When using catalytic ruthenium­(I) dicarbonyl propionate in the present system, IA was first isomerized to mesaconic acid, which was in turn decarboxylated to MAA (Figure ). Isomerization was confirmed by a control experiment subjecting dibutyl itaconate to the reaction conditions, thereby inhibiting decarboxylation via protection of the carboxylic acid moieties as butyl esters.…”
Section: Resultsmentioning
confidence: 99%